The note [large type] - Burke, Alafair (Random House Large Print, 2025)
"A vacation in the Hamptons goes terribly wrong for three friends with a complicated history. It was meant to be a harmless prank. Growing up, May Hanover was a good girl, always. Well-behaved, top of her class, a compulsive rule-follower. Raised by a first-generation Chinese single mother with high expectations, May didn't have room to slip up, let alone fail. Her friends didn't call her the Little Sheriff for nothing. But even good girls have secrets. And regrets. When it comes to her friendship with Lauren and Kelsey, she's had her fair share of both. Their bond - forged when May was just twelve years old - has withstood a tragic accident, individual scandals, heartbreak and loss. Now the three friends have reunited for the first time in years for a few days of sun and fun in the Hamptons. But a chance encounter with a pair of strangers leads to a drunken prank that goes horribly awry. When she finds herself at the center of an urgent police investigation, May begins to wonder whether Lauren and Kelsey are keeping secrets from her, testing the limits of her loyalty to lifelong friends. What had they gone and done? A propulsive thriller that explores of-the-moment social issues, The Note is a page-turner of the highest order from one of our greatest contemporary suspense writers"--